YOUNG PEOPLE AND FAMILY RURAL PROPERTIES IN THE WEST REGION OF PARANÁ (Gestão & Regionalidade, 2023)
In this article, we investigated how young people in the municipality of Assis Chateaubriand perceive the rural space and family rural property succession. The municipality of analysis has traditionally used land for agricultural production, and as a result, its economic development is influenced by it. A questionnaire was used to collect data from 153 young people from the municipality ranging in age from 14 to 29. To obtain the results, several steps were taken, including descriptive statistics, factor analysis, and content analysis. We found that young people do not see themselves as essential elements for the continuity of the family's rural property. In this sense, it is necessary to develop activities that encourage dialogues on the succession process in rural properties in the region, on the initiative of public or private agents